Pengaruh Tingkat Kecemasan dan Mekanisme Koping Ibu Primigravida terhadap Lamanya Kala I Persalinan Spontan - Sri Yunita Perangin Angin (EMBRIO, 2020)
Abnormal length of first stage of labor in nulliparous woman (first pregnant) can be influenced by severe anxiety during labor. The anxiety is related to maladaptive coping mechanism. The purpose of this study was to analyze the effect of anxiety level and coping mechanism of nulliparous woman on the length of first stage of labor. This research was analytical survey with explanatory research type. The samples consisted of 40 woman using total sampling technique. The date was gathered by using observation and interview sheets and analyzed using multiple logistic regression methods. The results showed that the level of anxiety (p=0,001) and coping mechanism (p=0,001)had a significant effect on the length of the first stage of labor, in which mother who had severe anxiety would have 13 time risk having abnormal length of first stage of labor (OP=13,49; 95%CI.1.94;93.81) compared with mother who had moderate anxiety, while maladaptive coping mechanisms would have 10 times risk having abnormal length of first stage of labor (OR=10,23;95%CI 1.67;62.60) compared with the adaptive coping mechanism. It is recommended that the husband should support their wives to reduce maternal anxiety during the labor process.